Pharmacokinetics, Urinary Excretion, and Pharmaco-Metabolomic Study of Tebipenem Pivoxil Granules After Single Escalating Oral Dose in Healthy Chinese Volunteers - Li, Zeyun; Su, Mei; Cheng, Weiyan; Xia, Jueyu; Liu, Shuaibing; Liu, Ruijuan; Sun, Suke; Feng, Luyao; Zhu, Xueya; Zhang, Xiaojian; Tian, Xin; Qu, Lingbo (Frontiers in Pharmacology, 2021)
Tebipenem pivoxil (TBPM-PI), an oral carbapenem antibiotic, has shown special advantages in pediatric infections and was in urgent need in China. Although pharmacokinetics, urinary excretion, and metabolite information of its active form tebipenem (TBPM) has been reported, ethnic differences may exist among the Chinese and Japanese population. By now, no systematic pharmacokinetics, urinary excretion, metabolites, or safety information has been revealed to the Chinese population. The purpose of the present work was to investigate abovementioned information of TBPM-PI granules after oral single ascending doses of 100, 200, and 400 mg in Chinese volunteers. Based on the pharmacokinetic study, the urine pharmaco-metabolomic analysis was conducted to reveal metabolomic interruptions and metabolite information. The study design was a single-center, open-label, randomized, single-dose pharmacokinetic study of 36 healthy volunteers (with half of them being male and the other half female). Time to maximum concentration (Tmax) was reached at 0.50, 0.50, or 0.67 h for 100, 200, or 400 mg, respectively. The linear pharmacokinetic characteristic of maximum plasma concentration (Cmax) was detected over 100–200 mg. The area under the concentration time curve (AUC) was proportional to the dose in the range of 100–400 mg. The maximum urinary excretion rate was detected at 0–1 or 1–2 h for dose of 100 or 200–400 mg. Cumulative amount of TBPM excreted in urine by 24 h accounted up to 90, 95, and 80% of dose administered for three groups, respectively. The pharmaco-metabolomic analysis revealed urine metabolic trajectory of deviation at 0–1 or 1–2 h and gradually regressing back to the pre-dose group at the following time periods. Urine metabolites from M1 to M4 were identified, indicating ethnic difference in metabolites among the Chinese or Japanese population. The current work proved safety and tolerance of single-dose administration of oral TBPM-PI in Chinese healthy volunteers over doses of 100–400 mg. All these results provide pharmacokinetics, urine excretion, urine metabolomics, urine metabolites, and safety information in healthy Chinese volunteers after oral single ascending doses of TBPM-PI, benefitting further development and clinical utilities.